The wealth of nations. Books I-III / Adam Smith with an introduction by Andrew Skinner - Adam Smith (London Penguin group, 1986)
'It is not from the benevolence of the butcher, the brewer, or the baker that we expect our dinner, but from their regard to their own interest.' With this landmark treatise on political economy, Adam Smith paved the way for modern capitalism, arguing that a truly free market - fired by competition yet guided as if by an 'invisible hand' to ensure justice and equality - was the engine of a fair and productive society. Books I-III of The Wealth of Nations examine the 'division of labour' as the key to economic growth, by ensuring the interdependence of individuals within society. They also cover the origins of money and the importance of wages, profit, rent and stocks. Smith's work laid the foundations of economic theory in general and 'classical' economics in particular, but the real sophistication of his analysis derives from the fact that it also encompasses a combination of ethics, philosophy and history to create a vast panorama of society.
Includes bibliographical references and indexes
Keywords: Political Economy; Economics; Economics; Electronic books